2019
DOI: 10.1038/s41598-019-52590-y
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of multiple monoamines receptors reduce insulin secretion from pancreatic β-cells

Abstract: Clinical use of olanzapine frequently causes severe hyperglycemia as an adverse effect. In this study, we elucidated mechanisms by which olanzapine reduced insulin secretion using the hamster pancreatic β-cell line HIT-T15. Reverse transcriptional-PCR analysis revealed expression of dopamine (D2, D3 and D4), serotonin (5-HT2A, 5-HT2B, 5-HT2C, and 5-HT6), and histamine (H1 and H2) receptors in HIT-T15 cells. Olanzapine decreased insulin secretion from HIT-T15 cells at clinically relevant concentrations (64–160 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 31 publications
0
26
0
Order By: Relevance
“…Some research found 5-HT 2C R is expressed in pancreas and islet of mouse and human (Bonhaus et al, 1995;Zhang et al, 2013;Nagata et al, 2019), although the precise expression is still controversial (Bennet et al, 2015;Bennet et al, 2016). Since previous results in our laboratory showed that 5-HT 2C R was expressed in mouse islets and MIN6 by Western blot and qPCR (Zhang et al, 2013).…”
Section: -Hydroxytryptamine 2c Teceptor Is Expressed In Mouse Islet β Cells and Min6 Cellsmentioning
confidence: 84%
See 2 more Smart Citations
“…Some research found 5-HT 2C R is expressed in pancreas and islet of mouse and human (Bonhaus et al, 1995;Zhang et al, 2013;Nagata et al, 2019), although the precise expression is still controversial (Bennet et al, 2015;Bennet et al, 2016). Since previous results in our laboratory showed that 5-HT 2C R was expressed in mouse islets and MIN6 by Western blot and qPCR (Zhang et al, 2013).…”
Section: -Hydroxytryptamine 2c Teceptor Is Expressed In Mouse Islet β Cells and Min6 Cellsmentioning
confidence: 84%
“…5-HT receptors include seven distinct families (at least 14 different receptors) and virtually all 5-HT receptors are G protein-coupled with the exception of 5-HT3 receptors (Wyler et al, 2017). Almost all 5-HT receptors in human islets (Amisten et al, 2013;Bennet et al, 2015) and in rodent islets (Ohara-Imaizumi et al, 2013;Bennet et al, 2016;Nagata et al, 2019) were found and activating of different 5-HT receptors also has contradictory effect on GSIS of pancreatic β cells (Zhang et al, 2013;Bennet et al, 2015;Kim et al, 2015;Bennet et al, 2016). Previous research in our laboratory found that activating of 5-HT 2C R on β cells by mCPP inhibited GSIS of mouse islets and MIN6 cells, which indicated that activation of 5-HT 2C R leaded to dysfunction of insulin secretion (Zhang et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of these, four target ion channels (tacrine hydrochloride, suloctidil, dyclonine hydrochloride, and IVM) ( Figure 2B and C ; Karlsson and Ahrén, 1992 ; Chatelain et al, 1984 ; Khanna et al, 2011 ; Chen and Kubo, 2018 ; Freeman et al, 1988 ; de Gaetano et al, 1976 ; Kornhuber et al, 2008 ; Sahdeo et al, 2014 ; Roghani et al, 1999 ; Ikeda, 2003 ). Five target seven-transmembrane G-protein coupled receptors (GPCRs) that signal through phospholipase C (PLC) and diacylglycerol (DAG) to activate insulin secretion and β-cell gene transcription (benzalkonium chloride, carbachol, isoetharine mesylate, pipamperone, and IVM) ( Figure 2B and C ; Chen and Kubo, 2018 ; Higashijima et al, 1990 ; Rinne et al, 2015 ; Bierman, 1983 ; Van Craenenbroeck et al, 2006 ; Nagata et al, 2019 ; Ratajewski et al, 2015 ; Ohtani et al, 2011 ). Similar to the hit compounds of our screen, our previous results showed that carbachol, a muscarinic G q -coupled receptor agonist, and the DAG mimetic PMA rescue insulin secretion in Bmal1 -/- islets ( Perelis et al, 2015 ).…”
Section: Resultsmentioning
confidence: 99%
“…Five target seven-transmembrane G-protein coupled receptors (GPCRs) that signal through phospholipase C (PLC) and diacylglycerol (DAG) to activate insulin secretion and β-cell gene transcription (benzalkonium chloride, carbachol, isoetharine mesylate, pipamperone, and ivermectin) ( Figs 2B-C) (17,(24)(25)(26)(27)(28)(29)(30). Similar to the hit compounds of our screen, our previous results showed that carbachol, a muscarinic Gq-coupled receptor agonist, and the DAG mimetic PMA rescue insulin secretion in Bmal1 -/islets (10).…”
Section: Nanoglo Luciferase Assay Substrate (Fig 1e)mentioning
confidence: 99%